MEMS packaging - Hsu, Tai-Ran (Institution of Engineering and Technology, 2004)
The book reviews developments in the following fields: fundamentals of MEMS packaging; joining and bonding technologies; sealing technology; microsystem packaging; automated microassembly; design for test; MEMS packaging in the life sciences; RF and optical packaging in telecommunications; and aerospace application.